La diabetes mellitus y su relación con las enfermedades cardiovasculares - Pérez Agramonte, Yaíma; Rodríguez Valido, Yannelis; Quesada Ravelo, Odalys (CorSalud, 2013)
La diabetes mellitus y su relación con las enfermedades cardiovasculares